KNOWLEDGE AND PREVENTIVE PRACTICES REGARDING COVID-19 INFECTION AMONG DENTISTS IN IAȘI - Balcoș Carina; Iulia Săveanu; Loredana Hurjui; Irina Grădinaru; Raluca Jipu; Dana Baciu; Andrei Nicolau; Dana Budală; Irina Zetu; Ramona Feier; Adina Oana Armencia (Romanian Dental Association for Education, 2020)
COVID-19 infection is a real challenge for medical practice due to the increased risk of contamination facilitated by airborne transmission. The aim of the study was to assess the level of knowledge and preventive practices on COVID-19 infection among dentists in Iasi. Material and methods: A cross-sectional study was conducted based on a questionnaire that was addressed to dentists with private practice in Iasi. The questionnaire included a number of 36 questions about the origin, epidemiology, etiology, mode of transmission, clinical features, diagnosis, clinical management, sources of information and educational information on COVID-19 infection. Results: The results of the study indicate a relatively good level of knowledge about the prevention methods to be used in dental practice. Conclusion: Healthcare professionals have demonstrated an adequate level of knowledge about COVID-19 infection in the dental environment, with a high percentage of correct answers. There is a strong need to implement regular educational programs and training programs on infection control practices such as COVID-19 in all healthcare professions.